1997
DOI: 10.1161/01.cir.96.10.3593
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins C and E Inhibit O 2 Production in the Pig Coronary Artery

Abstract: The present study is the first to show increased O2- production in injured vessels and to demonstrate that antioxidant vitamins reduce O2- production. These results suggest that beneficial effects of antioxidant vitamins in coronary artery disease are related, in part, to alterations in vessel redox state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 48 publications
7
97
0
3
Order By: Relevance
“…30 Bassenge et al 4 found oral ascorbate supplementation completely prevented the development of hemodynamic tolerance and upregulation of platelet activity in healthy volunteers. With the treatment and dosing regimes used in our subjects, a residual hemodynamic action of organic nitrates could be identified that was unaffected by oral ascorbate administration.…”
Section: Discussionmentioning
confidence: 99%
“…30 Bassenge et al 4 found oral ascorbate supplementation completely prevented the development of hemodynamic tolerance and upregulation of platelet activity in healthy volunteers. With the treatment and dosing regimes used in our subjects, a residual hemodynamic action of organic nitrates could be identified that was unaffected by oral ascorbate administration.…”
Section: Discussionmentioning
confidence: 99%
“…O xidative stress and production of both reactive oxygen species (ROS) and reactive nitrogen species (RNS) are thought to contribute to the pathophysiology of vascular diseases such as atherosclerosis (1,2) and restenosis (3)(4)(5)(6)(7)(8)(9). ROS have been implicated in many aspects of vascular injury and neointimal formation, including endothelial cell dysfunction, inflammatory cell recruitment, foam cell formation, and smooth muscle cell (SMC) proliferation (reviewed in ref.…”
mentioning
confidence: 99%
“…23,24 In addition, a dysfunctional interaction between the endothelium, platelets, and leukocytes results in a proinflammatory state with free radical production and microvascular plugging. 25,26 Attenuation of Ach-mediated increases in CBF with preserved responses to adenosine would imply a defect at the level of the endothelium. However, this does not clarify whether the diminished Ach response is attributable to abnormalities in stimulated NO production, decreased endothelium-derived hyperpolarizing factor or prostacyclin production, enhanced vasoconstrictors such as serotonin, 22 thromboxane, 27 and endothelin-1, 28 or a combination of these mechanisms.…”
Section: Vasomotor Responses After Pcimentioning
confidence: 99%